Breast Milk Lipidome Is Associated With Maternal Diet and Infants' Growth - Calvo-Lerma, Joaquim; Selma-Royo, Marta; Hervas, David; Yang, Baoru; Intonen, Linda; González, Sonia; Martínez-Costa, Cecilia; Linderborg, Kaisa M.; Collado, Maria Carmen (Frontiers in Nutrition, 2022)
Objectives: Fatty acid composition of breast milk is a relevant aspect related to the development of the lactating infant. The present study aimed at exploring correlations between dietary intake macro and micronutrients with the fatty acid profile in breast milk, and the possible implication in infants’ growth. Study design: Breast milk samples from a cohort of lactating women were collected 7-15 days postpartum. Fatty acid profile in triacylglycerols (TAG) and phospholipids (PL) – rich fractions were analysed by gas chromatography. Diet was registered during the third trimester of pregnancy by means of a food frequency questionnaire (FFQ). In addition, anthropometric measurements of infants were collected from gestation and up to 12 months postpartum. Results: The fatty acid profile in breast milk was characterised by median 37.4, 41.3 and 16.8% of saturated, monounsaturated and polyunsaturated fatty acids, respectively. From the dietary components, zinc, iron and B group vitamins were correlated positively with the proportion of total n-3 fatty acids in TAG and C20:5 n-3 in PL. Lycopene, vitamin E, zinc, and vitamin B2 showed a similar correlation with total PUFA, total n-6 fatty acids, C20:4 n-6 and C18:2 n-6 in TAG. Regarding food groups, nuts showed the strongest association with several PUFA both in TAG and PL, while the vegetables group was also positively associated with C18:3 n-3. Furthermore, the concentration of linolenic acid (C18:3 n-3) and palmitic acid (C16:0) were positively associated with increased length for age (LFA) and weight for age (WFA) at 12 months compared to birth [ΔLFA -0.16 (-0.85, 0.37); ΔWFA -0.26 (-0.77, 0.21)]. Conclusions: Mothers’ intake of nuts, dietary sources of zinc, iron and B group vitamins were identified as potential predictors of a high-unsaturated fatty acid profile in breast milk.